Estimating risks of common complex diseases across genetic and environmental factors: the example of Crohn disease. Issue 11 (27th July 2007) - Lewis, C M; Whitwell, S C L; Forbes, A; Sanderson, J; Mathew, C G; Marteau, T M
Abstract : Background: Progress has been made in identifying mutations that confer susceptibility to complex diseases, with the prospect that these genetic risks might be used in determining individual disease risk. Aim: To use Crohn disease (CD) as a model of a common complex disorder, and to develop methods to estimate disease risks using both genetic and environmental risk factors. Methods: The calculations used three independent risk factors: CARD15 genotype (conferring a gene dosage effect on risk), smoking (twofold increased risk for smokers), and residual familial risk (estimating the effect of unidentified genes, after accounting for the contribution of CARD15 ). Risks were estimated for high-risk people who are siblings, parents and offspring of a patient with CD. Results: The CD risk to the sibling of a patient with CD who smokes and carries two CARD15 mutations is approximately 35%, which represents a substantial increase on the population risk of 0.1%. In contrast, the risk to a non-smoking sibling of a patient with CD who carries no CARD15 mutations is 2%. Risks to parents and offspring were lower. Conclusions: High absolute risks of CD disease can be obtained by incorporating information on smoking, family history and CARD15 mutations. Behaviour modification through smoking cessation may reduce CD risk in these people.